Tracking of proinflammatory collagen-specific T cells in early and late collagen-induced arthritis in humanized mice. - Svendsen, P; Andersen, C; Willcox, N; Coyle, A; Holmdahl, R; Kamradt, T; Fugger, L (2004)
Rheumatoid arthritis is a chronic inflammatory disease associated with certain HLA-DR4 subtypes. The target autoantigen(s) is unknown, but type II collagen (CII) is a candidate, with a single immunodominant DR4-restricted 261-273 T cell epitope (CII(261-273)). In the present study, we have prepared HLA-DR4:CII(261-273) tetramers and analyzed peripheral blood, lymph node, and synovial fluid cells from DR4-transgenic mice with early and late collagen-induced arthritis to draw a fuller picture of the role of CII-reactive Th cells in disease development. Their frequencies increased approximately 20-fold in blood 1-2 wk postimmunization, and even more in acutely arthritic joints. Our data strongly suggest that CII-specific Th cells are necessary, but not sufficient for collagen-induced arthritis. The CII-specific Th cells displayed an activated proinflammatory Th1 phenotype, and their expansion correlated with onset and severity of arthritis and also with anti-CII Ab levels. Surprisingly, shortly after the first clinical signs of arthritis, activated HLA-DR4:CII tetramer(+) cells became undetectable in the synovial fluid and rare in the blood, but persisted in lymph nodes. Consequently, future human studies should focus on patients with early arthritis, and on their synovial cells, to re-evaluate the occurrence and pathogenic importance of CII-specific or other Th cells in rheumatoid arthritis.